China's Hong Kong : The Politics of a Global City. - Summers, Tim. (Newcastle Upon Tyne : Agenda Publishing, 2020)
In this new edition, Tim Summers brings his analysis of the politics of Hong Kong fully up to date and discusses the ramifications for the city of the mass demonstrations of June 2019 and the intensifying confrontational politics that has culminated in China's new security laws effectively criminalizing dissent in the city.
Intro -- Title Page -- Dedication -- Copyright Page -- Contents -- Preface to the second edition -- Note on transliteration -- Glossary and abbreviations -- Map -- Introduction -- 1. Hong Kong before 1997 -- 2. Implementing the handover settlement -- 3. Hong Kong's economy, globalization and the rise of China -- 4. The Occupy movement and its aftermath -- 5. International dimensions of the Hong Kong SAR -- 6. A year of protest -- 7. Hong Kong's future -- Timeline: Key dates in Hong Kong's political history -- Notes -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Hong Kong (China)-Relations-China.; Hong Kong (China)-Politics and government-1997-.; Electronic books